Luminescence and kinetics parameters of high sensitivity MgB4O7 phosphor co-doped with Tm and Dy. (September 2021) - González, P.R.; Ávila, O.; Escobar-Alarcón, L.; Mendoza-Anaya, D.
Abstract: This work reports the luminescence and kinetics parameters of high sensitivity MgB4 O7 phosphor co-doped with Tm and Dy ions (MgB4 O7 :Tm, Dy) obtained by the solution combustion technique. With the obtained material, sintered dosimeters in form of discs were made and subjected to 1223 K for 3 h and exposed to gamma radiation from a 60 Co source. It was found that these dosimeters show a sensitivity approximately 10 times higher than that shown by the commercial dosimeter TLD-100 (LiF:Mg, Ti). The kinetic parameters from three samples with different concentration of dopants were determined using the initial rise, peak shape and deconvolution methods. Initial rise and peak shape methods showed lower values than those found by the deconvolution method for the main peak (Peak 1). MgB4 O7 :Tm, Dy shows a wide linearity interval of TL response with respect to gamma dose and low coefficient of variability (1.5%). These results suggest that this new high sensitivity phosphor could be a promising material to be used in clinical dosimetry. Highlights: Tissue equivalent magnesium borate dosimeters co-doped with Tm and Dy ions were prepared and studied. Optimal sintering temperature was found to be 1223 K. High sensitivity MgB4 O7 phosphor was observed. The TL response of MgB4 O7 as a function of gamma dose was studied. Kinetic parameters determined by several methods are presented.